THU0210 Impact of Components of the Metabolic Syndrome on Knee Osteoarthritis Progression in the SEKOIA Study. (10th June 2014) - Eymard, F.; Edwards, M.; Parsons, C.; Cooper, C.; Petit Dop, F.; Reginster, J.Y.; Bruyere, O.; Richette, P.; Chevalier, X.
Abstract : Background: Recent studies have suggested that components of the metabolic syndrome might be involved in the pathophysiology of knee osteoarthritis (OA). However, their impact on joint space narrowing in patients with established knee OA is unknown. Objectives: We investigated the impact of each component of the metabolic syndrome on annual and 3-year joint space narrowing of medial tibiofemoral compartment. Methods: 559 men and women aged over 50 years with symptomatic knee OA (K&L 2-3) were recruited to the placebo arm of the SEKOIA study (98 centres; 18 countries). The presence or absence of type 2 diabetes, hypertension, and hyperlipidaemia was determined at baseline interview. Height and weight were measured and BMI calculated. Minimal medial tibiofemoral joint space on plain radiographs of the knee was assessed by two independent readers at baseline and then yearly for up to 3 years. Results: The mean (SD) age of participants was 62.8 (7.5) years. A total of 43.8% had a BMI>30, 6.6% had type 2 diabetes, 45.1% hypertension and 27.6% hyperlipidaemia. Those with type 2 diabetes had significantly higher joint space loss over the duration of the study than those without (0.63 and 0.35mm respectively; p=0.015). This relationship also held true for the assessment of annual joint space reduction (p=0.01). No evidence of an association was found between the remaining components of the metabolic syndrome (obesity, hypertension and hyperlipidaemia) and the joint space narrowing per year (p=0.99, p=0.49 and p=0.77 respectively) or over study duration (p=0.50, p=0.20 and p=0.28 respectively). The relationship between type 2 diabetes and both annual and 3-year joint space loss remained statistically significant after adjustment for BMI (p=0.011 and p=0.027 respectively). When sexes were examined separately, type 2 diabetes was a significant predictor of joint space loss in men but not women. Conclusions: Type 2 diabetes was a predictor of the rate of joint space narrowing in individuals with established knee OA. No such relationships were found for obesity, hypertension, and hyperlipidaemia. Further studies are required to replicate these findings and to explore a biological explanation. Disclosure of Interest: : F. Eymard: None declared, M. Edwards: None declared, C. Parsons: None declared, C. Cooper Consultant for: Servier, F. Petit Dop Employee of: Servier, J. Y. Reginster Grant/research support: Servier, Consultant for: Servier, O. Bruyere Consultant for: Servier, P. Richette: None declared, X. Chevalier Consultant for: Servier DOI: 10.1136/annrheumdis-2014-eular.2433